2006
DOI: 10.1097/01.tp.0000226076.04938.98
|View full text |Cite
|
Sign up to set email alerts
|

Association of High Pretransplant sIL-6R Plasma Levels with Acute Tubular Necrosis in Kidney Graft Recipients

Abstract: High pretransplant sIL-6R plasma levels are associated with an increased risk of ATN and might contribute to the development of ATN early posttransplant. Our data suggest that preactivation of the recipient's immune system increases the risk of ATN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 26 publications
(28 reference statements)
0
18
0
Order By: Relevance
“…High plasmatic levels of IL-6 production and urinary IL-6 concentration were associated with acute rejection episodes (1,25). High pretransplant soluble IL-6 receptor levels were associated with an increased risk of developing acute tubular necrosis (1). After reperfusion, gene expression of IL-6, amongst other cytokines, was significantly upregulated in renal tubuli compared to biopsies taken after cold ischemia (26).…”
Section: Il-6 Tnf-a Tgf-beta Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 85%
See 1 more Smart Citation
“…High plasmatic levels of IL-6 production and urinary IL-6 concentration were associated with acute rejection episodes (1,25). High pretransplant soluble IL-6 receptor levels were associated with an increased risk of developing acute tubular necrosis (1). After reperfusion, gene expression of IL-6, amongst other cytokines, was significantly upregulated in renal tubuli compared to biopsies taken after cold ischemia (26).…”
Section: Il-6 Tnf-a Tgf-beta Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 85%
“…They are expressed in the renal proximal tubular epithelial cells (RPTEC) upon activation, which play a major role in renal injury and dysfunction (21,22) and an increased production of IL-6 by RPTEC was detected in vitro in response to many diverse stimuli (23 (24). High plasmatic levels of IL-6 production and urinary IL-6 concentration were associated with acute rejection episodes (1,25). High pretransplant soluble IL-6 receptor levels were associated with an increased risk of developing acute tubular necrosis (1).…”
Section: Il-6 Tnf-a Tgf-beta Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%
“…Several studies have demonstrated that serum levels of sIL‐6R may offer prognostic information. The role of sIL‐6R as a prognostic factor has been recognized in multiple myeloma, kidney transplant, and primary hyperparathyroidism (25–27).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies documented the association of recipient pretransplant levels of different cytokines as the soluble interleukin 6 receptor (sIL-6R)[25] and the low soluble gp130 with post-transplant DGF.…”
Section: Biomarkers Of Ischemia-reperfusion Syndrome and Dgfmentioning
confidence: 99%